Efficient firm dynamics in a frictional labor market - Leo Kaas; Philipp Kircher (Institute for the Study of Labor (IZA), 2011)
The introduction of firm size into labor search models raises the question how wages are set when average and marginal product differ. We develop and analyze an alternative to the existing bargaining framework: Firms compete for labor by publicly posting long- term contracts. In such a competitive search setting, firms achieve faster growth not only by posting more vacancies, but also by offering higher lifetime wages that attract more workers which allows to fill vacancies with higher probability, consistent with empirical regularities. The model also captures several other observations about firm size, job flows, and pay. In contrast to bargaining models, efficiency obtains on all margins of job creation and destruction, both with idiosyncratic and aggregate shocks. The planner solution allows a tractable characterization which is useful for computational applications.
urn:nbn:de:101:1-201104113259
Keywords: E24; J64; L11; 330; labor market search; multi-worker firms; job creation and job destruction; Arbeitsuche; Arbeitsnachfrage; Unternehmenswachstum; Betriebsgröße; Beschäftigungseffekt; Arbeitsmarkttheorie; Theorie